Critical Thinking Ability and Student’s Personal Religious Beliefs: An Analysis of DBUS Model Implementation - Khasanah, Nur; Sajidan, Sajidan; Sutarno, Sutarno; Prayitno, Baskoro Adi; Walid, Ahmad (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2019)
The recent value integration of science and religion has become a topic of research in Indonesia, especially in developing critical-thinking skills and students’ personal religious belief. The purpose of this research is to see the results of the implementation of the DBUS (Discovery-Based Unity of Sciences) learning model analyzed in detail at each step of the learning. This research uses a qualitative approach with interactive analysis of data reduction, data presentation, and conclusion drawing. The research sample was 101 students and two biology lecturers from UIN Walisongo Semarang, 94 students and two biology lecturers from UIN Sunan Kalijaga Yogyakarta. The results of the analysis of this research show that, by implementing the DBUS learning model, students learn constructively, meaningfully, and can apply each syntax in the learning process to develop critical-thinking skills and students’ personal religious beliefs. The DBUS learning model becomes a way to integrate the value of science and religion in developing students' abilities to learn constructively and meaningfully so they can develop critical-thinking skills and personal religious beliefs (PRB).